Communicating science addressing contentious environmental issues: utilizing Luhmann's social systems theory - van Kempen, Anke; Feldpausch-Parker, Andrea M. (Frontiers in Communication, 2024)
For complex and socially contentious environmental issues such as climate change and disease prevention, science communication has proven difficult. As many science communication scholars have determined, education is not the only factor impacting the public's willingness to act upon or even accept scientific information. In this paper, we propose using Niklas Luhmann's theory of social systems as a framework for research in science and environmental communication. We argue that by focusing on the functions of relevant social systems, the occurrence of communication conflicts may be explained, and new approaches to overcome communication obstacles can be developed. In this paper, we provide examples of the theory's utility by looking at pertinent studies regarding relevant systems integral to addressing climate change and sustainability issues, as well as propose new subjects for exploration.